2000
DOI: 10.1007/s003350010094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ENU dosage on mouse strains

Abstract: The germline supermutagen, N-ethyl-N-nitrosourea (ENU), has a variety of effects on mice. ENU is a toxin and carcinogen as well as a mutagen, and strains differ in their susceptibility to its effects. Therefore, it is necessary to determine an appropriate mutagenic, non-toxic dose of ENU for strains that are to be used in experiments. In order to provide some guidance, we have compiled data from a number of laboratories that have exposed male mice from inbred and non-inbred strains or their F(1) hybrids to ENU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 23 publications
4
74
0
1
Order By: Relevance
“…A total of 71 mice have been injected by this procedure, and 61 of them have survived. This rate compares favorably with what has been reported in the literature for this procedure (Justice et al, 2000). We had proposed to inject 180 mice over the 3-year period of the grant, and we therefore have one-third of this number now available.…”
Section: Bodysupporting
confidence: 81%
“…A total of 71 mice have been injected by this procedure, and 61 of them have survived. This rate compares favorably with what has been reported in the literature for this procedure (Justice et al, 2000). We had proposed to inject 180 mice over the 3-year period of the grant, and we therefore have one-third of this number now available.…”
Section: Bodysupporting
confidence: 81%
“…Mouse mutagenesis, screening, and mapping G3 animals were generated according to the protocol of Justice et al (14). Blood samples were collected from all G3 animals and samples were stained for the expression of cell surface markers characteristic of T cell, B cell, monocyte, and neutrophil lineages.…”
Section: Methodsmentioning
confidence: 99%
“…A-T base pair substitutions and/or small intragenic lesions. Many of the mutant offspring produced by ENU-treated mice will, therefore, be hypomorph (partial loss of function), although gain-of-function as well as complete lossof-function mutants can also be expected (57,58). Several studies have demonstrated that the number of induced mutations depends on the dosage of ENU administered (59,60) and on the number of exons and length of coding sequences (61).…”
Section: Mutagenesis Screenmentioning
confidence: 99%